563 Measurement of Long-acting Natriuretic Peptide (Lanp) in Exacerbation of Asthma - Alkhalil, Michel (World Allergy Organization Journal, 2012)
BACKGROUND: Evidence exists that atrial natriuretic peptide (ANP) is a regulator of smooth muscle airway tone and is a potent bronchodilator and immune modulator in animals. Objective: Long-acting natriuretic peptide (LANP), encoded by the same gene and derived from the same pro-hormone as ANP, was measured in patients with acute asthma exacerbation pre- and post-treatment with systemic or inhaled glucocorticosteroids. METHODS: Measurement of LANP was obtained from plasma samples in 15 subjects with acute asthma exacerbation, by an enzyme immunoassay technique. A repeat measurement of LANP was obtained 5 to 7 and 10 to 14 days after initiation of treatment. RESULTS: No significant differences were found compared to baseline in plasma LANP level after treatment of the asthma exacerbation (P = 0.8904). The average LANP values were 2.12 higher in the oral glucocorticosteroid group versus the inhaled glucocorticosteroid group, (P = 0.0608). There was no significant difference in LANP levels between male and females (P = 0.5743), with antibiotic use (P = 0.9437), or with age (P = 0.6384). CONCLUSIONS: Plasma LANP level did not differ before and after treatment for an asthma exacerbation. Measuring plasma LANP pro-hormone was not helpful in assessing treatment outcome of asthma exacerbation.